PERCENTAGE OF INTERNAL OFFAL OF BROILER THAT WERE GIVEN PAPAYA (Carica papaya L.) SEED EXTRAGT THROUCH DRINKING WATER - N. W. E, Febriyanti; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the administration of papaya seed extract (Carica papaya L.) through drinking water on the percentage of internal organs of broilers. This research was conducted in Banjar Salanbawak Kelod, Salanbawak Village, Marga District, Tabanan Regency, Bali for 4 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications each containing 5 chickens so the total number of chickens used was 80. The treatments were PA (drinking water without papaya seed extract) as a control, PB (drinking water with 1% papaya seed extract), PC (drinking water with 2% papaya seed extract), and PD (drinking water with 3% papaya seed extract). The variables observed were the percentage of liver, the percentage of bile, the percentage of the heart, the percentage of the spleen and the percentage of the pancreas. The results showed that the treatment of giving 1%, 2% and 3% papaya seed extract (Carica papaya L.) had no significant effect (P>0.05) on the percentage of internal organs (liver, bile, heart, spleen and pancreas) of broiler chickens. From this study it can be concluded that the administration of 1%, 2% and 3% papaya seed extract (Carica papaya L.) through drinking water did not significantly affect the percentage of internal organs (liver, gallbladder, spleen and pancreas) in broilers. Keywords: Drinking water, Broiler,Papaya seed extract,Offal internal